A produção autônoma da prova na arbitragem - Terashima, Eduardo Ono (2024)
The purpose of this Thesis is to answer the following question: is the arbitral tribunal competent to process and judge non-urgent autonomous evidentiary demands? To answer it, the Thesis proposes to analyze the evolution of the concept of the autonomous right to evidence, analyzing Common Law systems, notably the United States and England, in the context of discovery and disclosure, making a parallel with the evolution of Evidentiary Law in the context of Civil Law systems, especially Brazil. In this context, we will analyze the institute of the action for the early production of evidence set forth by articles 381 and 382 of the Brazilian Code of Civil Procedure 2015. In this context, important aspects of the procedure will be addressed, especially its relevance as an instrument of social pacification and access to a fair legal order, as well as potential forms of abuse of the mechanism, which may violate parties’ fundamental rights. It will also address its jurisdictional nature and, consequently, the need to comply with the principles of adversarial proceedings and due process of law. Likewise, arbitration will be analyzed, going through its concepts and principles, highlighting its constitutional jurisdictional bases rooted on the adversarial process and due process of law, as well as its private nature, which is based on party autonomy. Finally, consolidating all these concepts, it will be analyzed whether the arbitral tribunal has jurisdiction to hear non-urgent claims seeking autonomous production of evidence with an underlying arbitration clause, concluding with a preliminary analysis of practical and theoretical issues that shall be intensely debated as the issue develops in both the practical and theoretical spheres